2014
DOI: 10.1111/desc.12267
|View full text |Cite
|
Sign up to set email alerts
|

Infants' use of social partnerships to predict behavior

Abstract: The experiences of social partners are important motivators of social action. Can infants use such experiences to make predictions about how social agents will behave? Sixteen-month-old infants were introduced to two social pairs. Initial events established within-pair cooperation as well as between-pair conflict involving an individual from each pair. Following these events, infants looked longer when between-pair members who had never previously interacted now cooperated—instead of conflicted—with each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 25 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…This demonstrates that a relationship between two people is a social currency comparable to other well-studied similarities (e.g., sharing a food preference: Liberman et al, 2014), and shows that infants notice and use this social information when observing others. These findings build upon recent evidence that 16-month-olds infer conflict between two individuals who have not interacted directly but whose partners were in conflict with each other (Rhodes et al, 2015). Predicting affiliation and conflict may emerge around the same age for infants, and future research could compare these types of interactions more directly.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This demonstrates that a relationship between two people is a social currency comparable to other well-studied similarities (e.g., sharing a food preference: Liberman et al, 2014), and shows that infants notice and use this social information when observing others. These findings build upon recent evidence that 16-month-olds infer conflict between two individuals who have not interacted directly but whose partners were in conflict with each other (Rhodes et al, 2015). Predicting affiliation and conflict may emerge around the same age for infants, and future research could compare these types of interactions more directly.…”
Section: Discussionsupporting
confidence: 82%
“…Caregiving is a moral obligation, like helping, which is centered on aid, so infants may reason about caregiving interactions in a similar manner to helping. In addition, infants at 16 months can track and infer conflict between two groups of characters: If they see characters cooperate with others within their group and then see some members of each group participate in inter-group conflict, infants infer that other members of the two groups will engage in intergroup conflict as well (Rhodes, Hetherington, Brink, & Wellman, 2015). No study reveals, however, whether infants’ reasoning about the structure of social networks supports inferences about affiliation between characters who have never been seen to interact directly.…”
Section: Introductionmentioning
confidence: 99%
“…A recent surge of research –outside of infants’ visual and social preferences—provides evidence infants have the cognitive capacities that may underlie conceptually rich social categorization. Infants can think about individual items as members of conceptual categories [68], form inductive inferences [6970], and track complex social relationships [7179]. Below we review evidence suggesting conceptually rich social categorization emerges early in life.…”
Section: The Origins Of Social Preferences and Social Categorization mentioning
confidence: 99%
“…First, extending prior research on young children's understanding of impersonal normativity (i.e., social norms; Rakoczy & Schmidt, ; Schmidt & Tomasello, ), the current experiments provide evidence for a simpler and more concrete form of normative understanding in the second year of life: second‐personal normativity which may emanate from joint intentional activities. Second, in contrast to much prior research that has found that infants develop descriptive expectations about others’ behavior (e.g., Powell & Spelke, ; Rhodes et al., ; Schmidt & Sommerville, ) and about the generalizability (to other persons, objects, etc.) of conventional forms (see Diesendruck & Markson, ), the present research suggests that infants also have a rudimentary understanding of the normative dimension of human action, forming second‐personal normative expectations about a partner's behavior in a triadic interaction.…”
Section: Discussionmentioning
confidence: 75%
“…As explained above, the two key main features of normativity are normative force and generalizability. Regarding the latter, much research suggests that during the first 2 years of life, infants develop descriptive expectations about agents’ social behavior (e.g., expecting equal resource allocation or behavior in line with social relationships; Geraci & Surian, ; Meristo, Strid, & Surian, ; Powell & Spelke, ; Rhodes, Hetherington, Brink, & Wellman, ; Schmidt & Sommerville, ) and about the generalizability (to other agents or objects) of conventional forms, such as object labels and functions (Buresh & Woodward, ; Diesendruck & Markson, ; Elsner & Pauen, ; Graham, Stock, & Henderson, ; Henderson & Scott, ; Henderson & Woodward, ). Thus, we predict that 18‐month‐olds may learn a novel action in a joint intentional activity with a first partner and generalize this action to a second dyad with another partner.…”
Section: Force Coming From the Collective “We”: Impersonal Normativitmentioning
confidence: 99%